Diagnostic accuracy of amyloid scintigraphy for the histopathological diagnosis of cardiac transthyretin amyloidosis – a retrospective Austrian multicenter study. (3rd October 2022) - Verheyen, N; Ungericht, M; Paar, L; Danninger, K; Schneiderbauer-Porod, S; Duca, F; Hoeller, V; Ablasser, K; Kiblboeck, D; Frick, M; Bonderman, D; Dierneder, J; et al.
Abstract: Background: Previous studies indicated that amyloid scintigraphy in combination with free light chain (FLC) assessment yields an excellent diagnostic accuracy for cardiac transthyretin (ATTR) amyloidosis (1). As a consequence, the diagnosis of ATTR amyloidosis is increasingly made without the actual gold-standard method endomyocardial biopsy (EMB). Whether this leads to misdiagnosis in real-world practice is currently underinvestigated. We aimed to describe the diagnostic accuracy of amyloid scintigraphy in a real world setting. Methods: Seven tertiary care centers throughout Austria agreed to participate in the study and performed a systematic retrospective medical records search from 2017 to 2020. Patients were included in case of available results of amyloid scintigraphy, FLC assessment and EMB, respectively. Amyloid scintigraphy was performed using a 99m-technetium-labelled tracer. Histological analysis was performed using immunohistochemistry. The number of submitted subjects with complete data per center ranged from 2 to 46. The patient number increased with years, with 15 patients investigated in 2017 and 32 in 2020. Results: We enrolled 101 patients (21% women) with a mean age of 73±9 years and median NT-proBNP (IQR) of 2694 (1601–5239) pg/ml (Table 1). An abnormal Perugini Score (ie. grade II or III) was present in 57 patients (56%) and FLC assessment was overall indicative of monoclonal protein in 60 patients (59%). Among patients with abnormal Perugini Score, 29 had FLC assessment indicative of monoclonal protein. The most common histopathological diagnoses were ATTR in 60 patients (59%) and cardiac light chain (AL) amyloidosis in 20 patients (20%). One further patient was diagnosed with concomitant AL and ATTR amyloidosis. Further diagnoses included ApoA4 (n=2) and AA amyloidosis (n=1), while cardiac amyloidosis was ruled out in 17 patients (17%). ATTR was diagnosed in 54 patients with Perugini Score II or III compared with 6 patients with Perugini < II, yielding a sensitivity of abnormal Perugini score for ATTR amyloidosis of 90%. Among patients with abnormal Perugini Score (n=57), ATTR was diagnosed in 55 patients, and AL amyloidosis in 3 (one had concomitant ATTR and AL), yielding a positive predictive value (PPV) of abnormal Perugini Score of 97% (Table 2). Two AL patients had Perugini Score of II and one had Perugini Score of III. When excluding patients with monoclonal gammopathy, the PPV of abnormal Perugini Score was 100%. Conclusion: Our data confirm a PPV of abnormal amyloid scintigraphy of 100% for cardiac ATTR amyloidosis when monoclonal gammopathy was excluded. mong patients with monoclonal gammopathy, one of ten patients with abnormal scintigraphy had AL amyloidosis as the underlying condition. Our data underscore that tissue biopsy and histopathological analysis should be performed in every patient with suspected amyloidosis and monoclonal gammopathy even in case of Perugini Score II or III. Funding Acknowledgement: Type of funding sources: None.